MINAT BELAJAR SISWA KELAS V SD N WINONG 01 PATI PADA PEMBELAJARAN ONLINE BERBASIS APLIKASI WHATSAPP - Risa Ardiani; Henry Suryo Bintoro; Ratri Rahayu Ratri Rahayu (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research aimed to investigate the learning interest of fifth grade students at SD N Winong 01 Pati. This research utilized qualitative descriptive method. This research was conducted at SD N Winong 01 Pati, Desa Winong, Kecamatan Winong, Kabupaten Pati. The focus of this research was studentsʼ learning interest towards WhatsApp-based online learning. The primary sources of data in this research were five 5th grade students at SD N Winong 01 Pati. In addition, the secondary sources of data were obtained through documentation of the students’ assignments and WhatsApp Group, articles, reference books, and other supporting data. The result of this research showed that students were often bored during learning at home. Moreover, teachers gave assignments without given materials or media to support the process of learning everyday. This caused the students less interested and not involved in learning. Students only responded and focused on the assignment given to them. The demand to submit the assignment everyday made the students motivated to learn and they did the assignment diligently. Besides, students also became more diligent and disciplined in learning and had a schedule of learning.